(untitled) (Nonconventional Technologies Review, 2024)
Thermoset polymer composite was made in an original version less expensive than the known techniques, in which alumina-borosilicate glass recycled from used laboratory glass was chosen as filler into the mixture of starting materials together with polyurethane resin as a matrix. The matrix/filler weight ratio was modified during the experiment from 0.67 to 1.22 and this change influenced the features of manufactured products. The temperature and time of the thermoset polymer curing process played an important role. It was opted for the electric heating of the material mixture up to 300-305 ℃ with the heating rate between 3.06-3.22 ℃/min, keeping at the maximum temperature for 100 min, and cooling in about 30 min. Results showed making a dense material type with relatively low heat conductivity. Tensile strength was around 40 MPa and compressive modulus of elasticity registered around 19 GPa, above the level of thermoplastic polymer.